A highly collateralized thalamic cell type with arousal-predicting activity serves as a key hub for graded state transitions in the forebrain. (November 2018) - Mátyás, Ferenc; Komlósi, Gergely; Babiczky, Ákos; Kocsis, Kinga; Barthó, Péter; Barsy, Boglárka; Dávid, Csaba; Kanti, Vivien; Porrero, Cesar; Magyar, Aletta; Szűcs, Iván; Clasca, Francisco; et al.
Abstract Sleep cycles consist of rapid alterations between arousal states, including transient perturbation of sleep rhythms, microarousals, and full-blown awake states. Here we demonstrate that the calretinin (CR)-containing neurons in the dorsal medial thalamus (DMT) constitute a key diencephalic node that mediates distinct levels of forebrain arousal. Cell-type-specific activation of DMT/CR+ cells elicited active locomotion lasting for minutes, stereotyped microarousals, or transient disruption of sleep rhythms, depending on the parameters of the stimulation. State transitions could be induced in both slow-wave and rapid eye-movement sleep. The DMT/CR+ cells displayed elevated activity before arousal, received selective subcortical inputs, and innervated several forebrain sites via highly branched axons. Together, these features enable DMT/CR+ cells to summate subcortical arousal information and effectively transfer it as a rapid, synchronous signal to several forebrain regions to modulate the level of arousal. Mátyás, Komlósi, et al. describe a highly specialized, calretinin-containing cell population in the dorsal medial thalamus. Connectivity, activity, and optogenetic manipulations identify these neurons as key mediators of forebrain arousal.